EMPLOYING MY NEXT WORDS E-BOOK AS THE LEARNING MEDIUM IN SPEAKING FOR BEGINNER CLASS - Liebnis, Vannia; Misrita, Misrita; Zulkarnain, Zulkarnain (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2025)
This study aimed to investigate students’ perceptions regarding the use of the English e-book MY NEXT WORDS as a learning medium in a speaking course for beginner-level students. The e-book, published by the Indonesian Ministry of Education and aligned with the Kurikulum Merdeka, was designed to enhance language acquisition through relevant and structured content. Employing a mixed-methods approach, this research gathered data from beginner speaking students at JJC Academy using questionnaires and short interviews. The findings revealed that most students held a positive perspective toward the use of the e-book. They found the content accessible, the activities engaging, and the topics relevant to real-life communication needs. Students also noted improvements in their speaking confidence and motivation to practice English. However, some limitations were highlighted, such as the limited novelty of vocabulary content for more advanced beginners. As a result, students suggested integrating additional multimedia components like interactive videos and games to enrich the learning experience. This study underscores the potential of digital resources like e-books in supporting English language development when thoughtfully implemented in the classroom.